Case report: Atypical young case of MV1 Creutzfeldt-Jakob disease with unusually long survival - Ahn, Lucie Yeongran; Cohen, Mark L.; Cali, Ignazio; Russell, Tia; Ludwig, Jessica; Jia, Xun; Bizzi, Alberto; Schonberger, Lawrence B.; Maddox, Ryan A.; Paul, Rohini; Ghazarian, Tania C.; Garcha, Jaspreet; et al. (Frontiers in Cellular Neuroscience, 2025)
Creutzfeldt-Jakob disease (CJD) is a rare, fatal, rapidly progressive neurodegenerative disease resulting from an accumulation of misfolded prion proteins (PrP). CJD affects 1–2 new individuals per million each year, and the sporadic type accounts for 90% of those cases. Though the median age at onset and disease duration vary depending on the subtype of sporadic CJD (sCJD), the disease typically affects middle-aged to elderly individuals with a median survival of 4–6 months. sCJD in younger individuals is extremely rare. Here, we present a 21-year-old female who died with a sporadic prion disease. She presented with psychiatric symptoms followed by a rapidly progressive neurocognitive and motor decline. EEG was negative for periodic sharp wave complexes; however, brain MRI was suggestive of prion disease. The cerebrospinal fluid (CSF) real-time quaking-induced conversion (RT-QuIC) assay was indeterminate. Neuropathologic examination at autopsy revealed severe neuronal loss and gliosis with secondary white matter degeneration but minimal spongiform changes and PrP deposits in the cerebellum and neocortex by immunohistochemistry. Absence of pathogenic mutations and methionine/valine heterozygosity at codon 129 of the prion protein gene (PRNP), atypical type 1 protease-resistant PrP that lacks or shows underrepresentation of the diglycosylated PrP isoform by western blot analysis, and no acquired prion disease risk factors resulted in a final diagnosis of atypical sCJD. Very young onset sCJD often has atypical clinical presentations and disease progression, neuropathological examination results, and/or laboratory test results that may confound diagnosis. It is critical to perform thorough, comprehensive evaluations to make an accurate diagnosis, which includes autopsy confirmation with histology, prion protein typing and prion gene sequencing.